1987
DOI: 10.1073/pnas.84.6.1585
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous electrical and optical measurements show that membrane fusion precedes secretory granule swelling during exocytosis of beige mouse mast cells.

Abstract: Mast cells show dramatic morphological changes when undergoing exocytosis. We have investigated whether the first of those morphological changes, swelling of the secretory granule, precedes-and therefore possibly initiates-secretion or whether it occurs after fusion of the granule and plasma membranes. We used cell membrane capacitance to detect the moment when granule and plasma membrane become continuous. We measured large capacitance increases, often preceded by transients in capacitance. The rise-times of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
216
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(230 citation statements)
references
References 21 publications
13
216
1
Order By: Relevance
“…However, results presented here and in previous studies (Zimmerberg et al, 1987;Brodwick et al, 1992;Jena et al, 1997) clearly demonstrate that vesicles can increase their volume beyond this limit. In one account for the apparent discrepancies between observed and predicted limits for increases in vesicle volume, it has been suggested that the membrane of dense core vesicles is flaccid against the dense core before swelling and that the extra membrane is used during membrane expansion (Zimmerberg et al, 1987;Brodwick et al, 1992).…”
Section: Mechanisms Regulating Vesicle Volume and Catecholamine Concementioning
confidence: 53%
See 1 more Smart Citation
“…However, results presented here and in previous studies (Zimmerberg et al, 1987;Brodwick et al, 1992;Jena et al, 1997) clearly demonstrate that vesicles can increase their volume beyond this limit. In one account for the apparent discrepancies between observed and predicted limits for increases in vesicle volume, it has been suggested that the membrane of dense core vesicles is flaccid against the dense core before swelling and that the extra membrane is used during membrane expansion (Zimmerberg et al, 1987;Brodwick et al, 1992).…”
Section: Mechanisms Regulating Vesicle Volume and Catecholamine Concementioning
confidence: 53%
“…3b, 4). If L-DOPA stimulates exocytosis, then it is possible that the increase in vesicle volume that is observed after treatment with L-DOPA could result from the influx of extracellular solution into the vesicles during membrane fusion (Breckenridge and Almers, 1987;Zimmerberg et al, 1987). However, on the basis of the morphological criteria used in previous studies of PC12 cells, all vesicle measurements were felt to reflect the morphology of dense core vesicles that were not actively involved in exocytosis (Watanabe et al, 1983;Madeddu et al, 1985;Hase et al, 1996).…”
Section: Effects Of L-dopa and Reserpine On Quantal Size And Vesiculamentioning
confidence: 92%
“…Indeed, amperometric measurements of current produced during oxidation of released secretory products from adrenal chromaffin cells (Wightman et al, 1991), mast cells (Alvarez de Toledo et al, 1993), PC12 cells (Chen et al, 1994), and mammalian neurons (Jaffe et al, 1998;Hochstetler et al, 2000) have shown that a single fusion event results in a single spike-like current. In contrast, early patch-clamp investigations of exocytosis on mast cells have suggested that neurotransmitter release proceeds in at least two main stages (Breckenridge and Almers, 1987;Zimmerberg et al, 1987). First, the vesicle connects to the extracellular medium via a stable fusion pore.…”
Section: Introductionmentioning
confidence: 99%
“…Mast cells were obtained from female Beige mice (C57BL/6N-bg) by peritoneal lavage, and cell degranulation triggered by 10 ,uM of GTP-y-S was studied as described [21]. To measure membrane capacitance we applied sinusoidally varying voltage with 1 kHz frequency and 50 mV peak-to-peak amplitude.…”
Section: Gtp-y-s-triggered Exocytosis In Beige Mouse Mast Cellsmentioning
confidence: 99%